Impact of ethical leadership and thriving at work on psychological well-being of employees: mediating role of voice behaviour - Yousaf, Khadija; Abid, Ghulam; Butt, Tahira Hassan; Ilyas, Sehrish; Ahmed, Saira (Business, Management and Economics Engineering, 2019)
Purpose – We investigated how thriving at work and ethical leadership affects the employee psychological well-being. Further, we also examined the mediating role of voice behaviour between thriving at work and employee psychological well-being as well as ethical leadership and employee psychological well-being. Research methodology – A quantitative research method was utilized to collect data from employees of a telecommunication company. SPSS and Process Macro were used for data analysis. Findings – Results demonstrated that thriving at work and ethical leadership are positively associated with employee psychological well-being. Furthermore, the employee voice behaviour acts as a mediator between thriving at work, ethical leadership and employee well-being. Research limitations – All of the data in this study were collected from single source i.e., employees of information technology industry and also specific to a metropolitan city like Lahore. Further, study has a very limited representation of the females. Practical implications – the findings suggest that organizations should create such an environment where managers are able to have positive verbal interactions with employees that may facilitate their well-being and makes them satisfied with their jobs. Originality/Value – This study is one of the first studies to investigate the association between voice behaviour, thriving at work, employee psychological as well as psychological well-being.